63, XX, SRY‐negative, pseudohermaphroditism in a Somali wild ass (Equus asinus somalicus). Issue 3 (25th September 2020) - Gillis, James; Bercier, Marjorie; Rattner, Francine K; Citino, Scott
SUMMARY: A six‐month‐old Somali wild ass ( Equus asinus somalicus ) scheduled for a routine health exam presented with masculinised external genitalia, which included an enlarged phallus‐like clitoris that was not connected to the urethra. A gonadectomy was conducted to sterilise the individual. Histological examination of the gonads revealed normal ovarian tissue with a recent corpus luteum, developing follicles and no testicular tissue. Karyotype analysis classified the individual as female, 63, XX, sex‐determining region Y‐negative, which is normal for a female Somali wild ass. Serum testosterone was analysed via enzyme immunoassay and was found to be below detectable concentrations. Although similar cases have been reported in domestic equids, this is the first case of intersex reported in a non‐domestic equid.